PREGNANCY INDUCED HYPERTENSION - Arauzo Chuco, Godofredo (2015)
The outcomes of care of 74 patients with pregnancy induced hypertension found in 18,369 births in the Hospital of Tingo Maria from 1 January 1971 to December 31, 1984 are discussed, giving an incidence of 0.4% (preeclampsia 0.32% and 0.08 eclampsia); nulliparous 78.38% 48.69% adolescents, average age 22.45 years, 37.12 weeks gestational age, parity 0.95 and average weight of 2945 grams products. Birth vaginally resolved 87.84% and 12.16% cesarean. Maternal and fetal mortality 6.25% 18.75%. Treatment should be done with hospitalized patient, competent staff with magnesium sulfate. We use hypotensive when the minimum rises of 120 mm / Hg. and do not drop below 90 mm / Hg. We do not use water or diuretics or restrict sales. With term fetus we accelerate the delivery. We use only for obstetric cesarean indications. Prenatal care is essential to reduce maternal-fetal morbidity and mortality.